Anxiety, Stress and Depression in COVID-19 Survivors From an Italian Cohort of Hospitalized Patients: Results From a 1-Year Follow-Up - Gramaglia, Carla; Gattoni, Eleonora; Gambaro, Eleonora; Bellan, Mattia; Balbo, Piero Emilio; Baricich, Alessio; Sainaghi, Pier Paolo; Pirisi, Mario; Binda, Valeria; Feggi, Alessandro; Jona, Amalia; Marangon, Debora; et al. (Frontiers in Psychiatry, 2022)
Background. Beyond the most common respiratory clinical features of COVID-19, mental health-related symptoms can persist over time. A recent meta-analysis underlined that mental health sequalae are relevant issue for COVID-19 survivors. The following prevalence were reported: 20% for Post-Traumatic Stress Disorder, 22% for anxiety, 36% for psychological distress and 21% for depression. In the context of a multi-disciplinary follow-up project, we already investigated the mid-term (4 months) psychiatric outcomes of the infection in a sample of COVID survivors. Patients were re-assessed after 1-year since hospital discharge. Methods. Follow-up conducted after 1 year involved 196 individuals recovered from COVID-19. In the context of a multi-disciplinary approach, patients' assessment included both a clinical interview performed by an experienced psychiatrist, trained in the use of the Mini-International Neuropsychiatric Interview to assess the presence of anxiety, stress and depressive symptoms and the following self-administered questionnaires: Beck Anxiety Inventory, Beck Depression Inventory-II, Resilience Scale for Adults, Impact of Event Scale, CoViD-19 Peritraumatic Distress Index. Results. Anxiety (p<0.0001) and depressive (p<0.0003) symptoms registered at the clinical interview showed a significant improvement from the 4-months to the 12-months follow-up. The logistic regression model showed that female gender (p=0.006), arterial hypertension (p=0.01), obesity (0.04), anxiety (p<0.0001) and depressive (p=0.02) symptoms at the 4-months follow-up were associated with the persistence of anxiety symptoms at 12 months. At logistic regression analysis the female gender (p=0.02) and depressive symptoms at the 4-months follow-up (p=0.01) were associated with depressive symptoms after 12 months. Conclusions. As in our previous study (4-months follow-up), the severity of the disease in the acute phase is not a determining factor in identifying subjects particularly at risk of developing clinically relevant anxiety and depression as a consequence of COVID-19 disease. Findings from the logistic regressions suggest that in COVID survivors the factors that most affect depression and anxiety after 12 months are female gender, the presence of anxiety and depression after 4 months and some physical symptoms, not necessarily COVID-related, while the impact of the infection and consequent hospitalization for COVID-19 would no longer represent a relevant issue for depressive symptoms, compared to other general factors.